El documento alterado: estrategias de contramemoria. Sobre Los desastres de la guerra fría de Fredi Casco - Lia Colombino (Centre de Recherches sur les Mondes Américains, 2014)
This paper explores in an introductory way the operations triggered from the concern regarding the past of Paraguay, mainly that recent past – Stroessner dictatorship –. Trauma and grief, documents and traces, and the manner in which they can or cannot be inscribed locally. From the question about the recent memory in Paraguay, we explore Fredi Casco’s artwork, playing whit the way art reads memory, develop memory. Also launchanother operation on the table: countermemory, a strategy the artist found in order to disarrange the narration of a past that that has not gone away.